Sanitisation of wine-ageing barrels using near Ultraviolet radiation - Maria C. Portillo; Erick Alberto Tena-García; Eugenia Vila; José M. Rigol; Nicolas Rozès (IVES Technical Reviews, 2023)
The ageing of wine in oak barrels represents a critical stage in winemaking at which product alteration can occur due to bacteria, yeasts or fungal growth. The control of microorganisms, such as yeasts of the Brettanomyces genus (Guzzon et al, 2011) and acetic acid bacteria (Kocijan et al, 2021), is of great importance, since the alterations that they can cause in wine can be very serious and cause great economic losses.